Type 2 diabetes mellitus and the risk of abnormal spermatozoa: A Mendelian randomization study - Dai, Mengyuan; Guo, Weijie; Zhu, San; Gong, Guidong; Chen, Mei; Zhong, Zhuoling; Guo, Junling; Zhang, Yaoyao (Frontiers in Endocrinology, 2022)
Abnormal spermatozoa can not only reduce the fertilization rate, but also prolong the natural conception time and even increase the risk of spontaneous miscarriage. Diabetes mellitus (DM) has become a major global health problem, and its incidence continues to rise, while affecting an increasing number of men in their reproductive years. Type 2 Diabetes Mellitus (T2DM), accounting for about 85-95% of DM, is closely related to the development of sperm. However, the exact association between T2DM and abnormal spermatozoa remains unclear. Herein, we designed a Two-sample Mendelian randomization (MR) study to explore the causal association between T2DM and abnormal spermatozoa risk in European population data which come from the GWAS summary datasets. We selected 9 single nucleotide polymorphisms (SNPs) of T2DM (exposure data) as instrumental variables (IVs), and then retrieved the suitable abnormal spermatozoa genome-wide association study (GWAS) data of European from Ieu Open GWAS Project database which includes 915 cases and 209,006 control as the outcome data. Our results indicate that strict T2DM might not result in a higher risk of abnormal spermatozoa genetically in Europeans (OR: 1.017, 95% confidence interval (CI): 0.771-1.342, p=0.902). Our findings demonstrate that only T2DM may not explain the relatively higher risk of abnormal spermatozoa in men with it in Europeans. In subsequent studies, more comprehensive and larger samples need to be studied to reveal the relationship and potential mechanism between T2DM and abnormal spermatozoa.